Implications of Ankyloglossia on Breastfeeding. Issue 2 (March 2019) - Hill, Rebecca
Abstract: Objective: The purpose of this integrative review was to synthesize the literature on the relationship between infant breastfeeding and ankyloglossia. Data Sources: The search terms tongue-tie or ankyloglossia and breastfeeding were used via CINAHL, Ovid MEDLINE, Health Reference Academic, and PsycINFO. Primary research articles and clinical reviews were considered in the search parameters. Study Selection: Searches yielded 201 articles written in English and published between 1999 and 2018. After screening, 50 full-text articles were assessed for eligibility, 43 of which were omitted for irrelevance. Three qualitative and four quantitative studies remained for inclusion in the review. Data Extraction: Studies were reviewed for information on the relationship between ankyloglossia and breastfeeding. Studies examining results of ankyloglossia treatment were omitted. Preferred Reporting Items of Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used. Data Synthesis: Analysis revealed a varied degree of difficulties with breastfeeding when the infant has ankyloglossia. Prevalence is uncertain due to lack of universal screening guidelines, and infrequent use of screening tools. No studies were found that examined psychological ramifications of feeding difficulties with ankyloglossia. There are no validated screening tools for ankyloglossia. Conclusion: More research is necessary on effects of breastfeeding difficulties of infants with ankyloglossia on the mother–infant relationship. A reliable screening tool needs to be developed and validated. Education for nurses to assess infants with ankyloglossia in a systematic fashion should be explored. Investigation of psychological sequelae, including maternal stress, postpartum depression, and mother–infant bonding is an important next step in the research of infants with ankyloglossia. Abstract : Ankyloglossia, also known as tongue tie, is a relatively common congenital anomaly with an overall prevalence of 4.5% to 16% of newborns. It often affects breastfeeding duration and pain. There are no validated screening tools for early detection. An integrated review of the literature on the relationship between ankyloglossia and breastfeeding is provided and important gaps in knowledge identified.